Dual‐Intermetallic Heterostructure on Hierarchical Nanoporous Metal for Highly Efficient Alkaline Hydrogen Electrocatalysis - Shi, Hang; Dai, Tian‐Yi; Sun, Xin‐Ying; Zhou, Zhi‐Lan; Zeng, Shu‐Pei; Wang, Tong‐Hui; Han, Gao‐Feng; Wen, Zi; Fang, Qian‐Rong; Lang, Xing‐You; Jiang, Qing (Advanced materials (Weinheim), 2024)
Constructing well‐defined active multisites is an effective strategy to break linear scaling relationships to develop high‐efficiency catalysts toward multiple‐intermediate reactions. Here, dual‐intermetallic heterostructure composed of tungsten‐bridged Co3W and WNi4 intermetallic compounds seamlessly integrated on hierarchical nanoporous nickel skeleton is reported as a high‐performance nonprecious electrocatalyst for alkaline hydrogen evolution and oxidation reactions. By virtue of interfacial tungsten atoms configuring contiguous multisites with proper adsorptions of hydrogen and hydroxyl intermediates to accelerate water dissociation/combination and column‐nanostructured nickel skeleton facilitating electron and ion/molecule transportations, nanoporous nickel‐supported Co3W–WNi4 heterostructure exhibits exceptional hydrogen electrocatalysis in alkaline media, with outstanding durability and impressive catalytic activities for hydrogen oxidation reaction (geometric exchange current density of ≈6.62 mA cm−2) and hydrogen evolution reaction (current density of ≈1.45 A cm−2 at overpotential of 200 mV). Such atom‐ordered intermetallic heterostructure alternative to platinum group metals shows genuine potential for hydrogen production and utilization in hydroxide‐exchange‐membrane water electrolyzers and fuel cells. Dual‐intermetallic heterostructure composed of tungsten‐bridged Co3W and WNi4 intermetallic compounds seamlessly integrated on nanoporous Ni skeleton exhibits exceptional activities and durability for hydrogen evolution and oxidation reactions. Such dual‐intermetallic heterostructure enables interfacial atoms to configure multisites to accelerate water dissociation/combination, demonstrating the feasibility to construct well‐defined active multisites for multiple‐intermediate reactions based on intermetallic compounds.